2016
DOI: 10.1016/j.jglr.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change and water resources development on the declining inflow into Iran's Urmia Lake

Abstract: Urmia Lake, the world second largest hypersaline lake, has decreased in size over recent decades primarily because inflow has diminished. This has caused serious socio-environmental consequences similar to those of the Aral Sea disaster. By using the Variable Infiltration Capacity (VIC) model, this study estimates the relative contributions of climate change and water resources development -which includes construction of reservoirs and expansion of irrigated areas -to changes in Urmia Lake inflow over the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 41 publications
3
76
0
2
Order By: Relevance
“…However, it is worth noticing that despite the fact that the amount of R a is maximum during summer, the maximum amount of CSR S is received in May at the stations Urmia and Bandarabbas. This fact may be due to higher amount of aerosol and/or humidity stemming from evaporation from the Lake of Urmia (Stone, 2015;Shadkam et al, 2016a;Shadkam et al, 2016b;Moghaddasi et al, 2017) and Persian Gulf during summer, which may lead to more scattering effects at the stations Urmia and Bandarabbas, respectively. The results of the trend analysis of annual mean CSR S during 1998-2015 are represented in Table 2.…”
Section: Csr S and Its Relationship With Asr Smentioning
confidence: 99%
“…However, it is worth noticing that despite the fact that the amount of R a is maximum during summer, the maximum amount of CSR S is received in May at the stations Urmia and Bandarabbas. This fact may be due to higher amount of aerosol and/or humidity stemming from evaporation from the Lake of Urmia (Stone, 2015;Shadkam et al, 2016a;Shadkam et al, 2016b;Moghaddasi et al, 2017) and Persian Gulf during summer, which may lead to more scattering effects at the stations Urmia and Bandarabbas, respectively. The results of the trend analysis of annual mean CSR S during 1998-2015 are represented in Table 2.…”
Section: Csr S and Its Relationship With Asr Smentioning
confidence: 99%
“…The results of some research studies [7][8][9][10] also confirmed that human factors have a greater impact on drying Urmia Lake than climatic factors. Shadkam et al [11] examined the effects of climate change and the development of water resources (including constructing dams and increased irrigated agriculture) on the reduction of inflow to the Urmia Lake during the period of 1960 to 2010. The results showed that the annual inflow to Lake Urmia decreased by 48% during the studied period.…”
Section: Introductionmentioning
confidence: 99%
“…The Nazloo-Chai River, 25 km long, irrigates 32 400 ha of lowlands of the Nazloo District and rises from the slopes of the mountains of the Iran-Turkey border, flows from west to east and finally discharges into Lake Urmia (Taifeh Rezaee et al, 2014). The study area has an arid to semi-arid climate (Shadkam et al, 2016). The average annual rainfall was 333 mm in the period 1951-2015.…”
Section: Description Of the Study Areamentioning
confidence: 99%